Nickel and chromium levels in the saliva of a Saudi sample treated with fixed orthodontic appliances - Nabeel F. Talic; Hasan H. Alnahwi; Ali S. Al-Faraj (Saudi Dental Journal)
Aim: The aim of this study was to measure the amount of nickel (Ni) and chromium (Cr) released into the saliva of Saudi patients treated with fixed orthodontic appliances. Materials and methods: Ninety salivary samples were collected in a cross-sectional manner. Forty samples were collected from patients (17 males, 23 females) with fixed orthodontic appliances after different periods of orthodontic treatment ranging from the first month and up to 32 months into treatment. The fixed orthodontic appliance consisted of 4 bands, 20 stainless steel brackets, and upper and lower nickel titanium or stainless-steel arch wires. The other 50 samples were collected from people without appliances (24 males, 26 females). Samples were analyzed using Inductive Coupled Plasma/Mass Spectrometry and Inductively Coupled Plasma Optical Emission Spectroscopy to measure Ni and Cr levels, respectively. Student’s t-test was used to compare Ni and Cr levels in the treated and untreated control groups. Results: The mean Ni level was 4.197 μg/L in the experimental group and 2.3 μg/L in the control group (p < 0.05). The mean Cr level was 2.9 μg/L in the experimental group and 3.3 μg/L in the control group (p < 0.05). Conclusion: Fixed orthodontic appliances resulted in a non-toxic increase in salivary levels of Ni, but no change in Cr levels. Duration of orthodontic treatment did not affect Ni and Cr levels in the saliva. Keywords: Nickel, Chromium, Saliva, Fixed orthodontic appliance